The role of ultrasound and colour doppler in the diagnosis of appendicitis - Sami Ahmed Ahmed Elhinnawi; Aboalmagd Mohamed Albohy; Mohammed Faheem Mostafa (Cairo : Sami Ahmed Ahmed Elhinnawi, 2020)
It is one of the most common causes of acute abdominal pain, with a lifetime risk of 8.6% in males and 6.7% in females. It is the most common non-obstetric surgical emergency during pregnancy, with an incidence of 6.3 per 10,000 pregnancies during the ante-partum period (compared with 9.6 per 10,000 in non-pregnant persons) and increasing to 9.9 per 10,000 post-partum.More than 300,000 appendectomies are performed each year in the United States, and less than 10% result in the removal of a normal appendix. Appendicitis is thought to be caused by luminal obstruction from various etiologies, leading to increased mucus production and bacterial overgrowth, resulting in wall tension and, eventually, necrosis and potential perforation
Thesis (M.Sc.) - Cairo University - Faculty of Medicine - Department of Radio-Diagnosis
Issued also as CD
Keywords: Colour doppler; Diagnosis of appendicitis; Ultrasound